Effects of Workplace Harassment and Favouritism on Staff Performance in Nigeria (International Journal of Scientific Research and Management (IJSRM), 2022)
Workplace harassment and favouritism occupy a commonplace in most organizations and broadly practiced in both public and private sector. Regardless of the avalanche of empirical studies in this area, there is dearth of empirical investigations on the effect workplace harassment and favouritism has on employee performance in the Nigerian context. The main purpose of this paper is to investigate the effect of workplace harassment and favouritism on staff performance. The paper proposed two objectives and research hypotheses and survey method was employed via structured questionnaire administered to 100 staff of Benin Electricity Distribution Company (BEDC) Headquarters without recourse to age, gender, rank, and department. The simple linear regression tool was used in validating the research hypotheses of the study. Findings indicated that workplace harassment and favouritism statistically and significantly affect staff performance. The result implies that the act of harassment and favouritism is being practiced among employees and do not mean well for employee performance. It was therefore commended among others that management of BEDC should make strategic efforts and put measures to completely devoid the workplace of all injustices and also set up adequate and fair human resource (HR) systems that work in order to promote staff performance in Nigeria.